Education.com
Try
Brainzy
Try
Plus
Courtney_12_9
Courtney_12_9 asks:
Q:

How do you solve this type of problem: (1 3/5)y-(1 3/10)y =?

In Topics: Helping my child with math
> 60 days ago

|

Answers (1)

Maverick
Maverick , Teacher writes:
I am assuming you meant 1 3/5( one and three fifth)  as supposed to  13/5 (thirteen  fifth).

As a first step, let's convert the mixed fraction into an improper one.

1 3/5 = (5*1 + 3) /5 = 8/5

Similarly  1  3/10 = (10*1 + 3) /10 = 13/10

The problem simplifies to

(8/5)y - (13/10)y.

Since they are like terms, we can simplify them further.
Let's make the denominators the same by multiplying top and bottom of the first fraction by 2.  

( (8*2)/(5*2) ) - (13/10) y

(16/10)y - (13/10)y = (3/10)y

Cheers :)

Did you find this answer useful?
1
yes
1
no
Answer this question